Conceptual competence in psychiatric training: building a culture of conceptual inquiry - Awais Aftab; John Z. Sadler; Brent M. Kious; G. Scott Waterman (BJPsych Bulletin)
Building a culture of conceptual inquiry in psychiatric training requires the development of conceptual competence: the ability to identify and examine assumptions that constitute the philosophical foundations of clinical care and scientific investigation in psychiatry. In this article, we argue for the importance of such competence and illustrate approaches to instilling it through examples drawn from our collective experiences as psychiatric educators.